Identification of Food Types of Ghost Crabs (Ocypode kuhlii L.) in The Intertidal Zone of Peudawa Beach, East Aceh - Dwi Syaravicena; Sri Jayanthi; Aini Ramadila; Suci Nurlida Sapitri; Devi Anisa; Viska Anisa Sabrini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Ghost crabs are one of the arthropod animals that live in coastal ecosystems and are one of the key species that have a very important role in maintaining ecological balance. Here the author refers to the abundance of ghost crabs and the types of food eaten by ghost crabs, this is because there are still many who do not know about the types of ghost crab hands and the abundance of ghost crab hands and the abundance of ghost crabs on an east aceh beach. The type of research used was quantitative research with a random sampling method which was carried out on November 25 2023. From the results of this crab density research, there were 100 individuals with a translation size of 254M and a density index of 1,96 D at 40 54’’ 9’ N 970 51’’ 2’ T. Aceh Regency Timur, the types of food for ghost crabs are Zooplankton, Phytoplankton and Bacterioplankton. The conclusion of this research is that the existence of this crab population is greatly influenced by the condition of the beach which is its habitat. Natural beaches usually find many ghost crabs because the food chain process is still maintained.